Early virological suppression with three-class antiretroviral therapy in HIV-infected African infants. - Prendergast, A; Mphatswe, W; Tudor-Williams, G; Rakgotho, M; Pillay, V; Thobakgale, C; McCarthy, N; Morris, L; Walker, B; Goulder, P (2008)
OBJECTIVES: Infants infected with HIV-1 perinatally despite single-dose nevirapine progress rapidly. Data on treatment outcome in sub-Saharan African infants exposed to single-dose nevirapine are urgently required. This feasibility study addresses efficacy of infant antiretroviral therapy in this setting. METHODS: HIV-infected infants in Durban, South Africa, received randomized immediate or deferred (when CD4 cell count reached <20%) four-drug antiretroviral therapy (zidovudine/lamivudine/nelfinavir/nevirapine). Genotyping for non-nucleoside reverse transcriptase inhibitor (NNRTI) resistance was undertaken pre-antiretroviral therapy. Monthly follow-up to 1-year post-antiretroviral therapy included viral load, CD4 cell count and verbal/measured adherence monitoring. RESULTS: All 63 infants were exposed to single-dose nevirapine. Twenty-one out of 51 (39%) infants with baseline genotyping results had NNRTI resistance (most frequently Y181C; 20%). Forty-three infants were randomized to immediate antiretroviral therapy (ART): three withdrew pre-antiretroviral therapy; 36 out of 40 completed 1-year of ART. Twenty infants received deferred ART: 17 reached CD4 cell counts less than 20% (median d99) and 13 out of 17 started antiretroviral therapy in year 1. Verbal and measured adherence was 99% and 95%, respectively. One-year post-ART, 49 out of 49 (100%) infants had a viral load less than 400 copies/ml; 46 out of 49 (94%) had viral load less than 50 copies/ml. Ten infants (20%) required second-line ART due to virological failure or tuberculosis treatment, therefore 39 out of 49 (80%) achieved viral load less than 400 copies/ml by intention-to-treat. Time to viral load less than 50 copies/ml correlated with maternal CD4 cell count (r = -0.42; P = 0.005) and infant pre-ART viral load (r = 0.64; P < 0.001). NNRTI mutations had no significant effect on virological suppression. Infants starting immediate compared with deferred ART had fewer illness episodes (P = 0.003), but no significant difference in virological suppression. CONCLUSION: Excellent adherence and virological suppression are achievable in infants, despite high-frequency NNRTI mutations and rapid disease progression. Infants remain relatively neglected in roll-out programmes and ART provision must be expanded.